Joint measurement of the atmospheric muon flux through the Puy de Dôme volcano with plastic scintillators and Resistive Plate Chambers detectors. Issue 11 (14th November 2015) - Ambrosino, F.; Anastasio, A.; Bross, A.; Béné, S.; Boivin, P.; Bonechi, L.; Cârloganu, C.; Ciaranfi, R.; Cimmino, L.; Combaret, Ch.; D'Alessandro, R.; Durand, S.; et al.
Abstract: The muographic imaging of volcanoes relies on the measured transmittance of the atmospheric muon flux through the target. An important bias affecting the result comes from background contamination mimicking a higher transmittance. The MU‐RAY and TOMUVOL collaborations measured independently in 2013 the atmospheric muon flux transmitted through the Puy de Dôme volcano using their early prototype detectors, based on plastic scintillators and on Glass Resistive Plate Chambers, respectively. These detectors had three (MU‐RAY) or four (TOMUVOL) detection layers of 1 m 2 each, tens (MU‐RAY) or hundreds (TOMUVOL) of nanosecond time resolution, a few millimeter position resolution, an energy threshold of few hundreds MeV, and no particle identification capabilities. The prototypes were deployed about 1.3 km away from the summit, where they measured, behind rock depths larger than 1000 m, remnant fluxes of 1.83±0.50(syst)±0.07(stat) m −2 d −1 deg −2 (MU‐RAY) and 1.95±0.16(syst)±0.05(stat) m −2 d −1 deg −2 (TOMUVOL), that roughly correspond to the expected flux of high‐energy atmospheric muons crossing 600 meters water equivalent (mwe) at 18° elevation. This implies that imaging depths larger than 500 mwe from 1 km away using such prototype detectors suffer from an overwhelming background. These measurements confirm that a new generation of detectors with higher momentum threshold, time‐of‐flight measurement, and/or particle identification is needed. The MU‐RAY and TOMUVOL collaborations expect shortly to operate improved detectors, suitable for a robust muographic imaging of kilometer‐scale volcanoes. Key Point: The feasibility of muon imaging of km thick volcanoes was checked using two different detectors